Optimalisasi Budidaya Jamur di Dusun Sukosreno: Inovasi Teknologi dan Pemberdayaan Masyarakat - Ananta, Muhammad F.; Pratama, Anugerah R. A.; Fajrin, Faisha N.; Kusumayana, Brian; Thani, Felicia A.; Zaini, Muhammad; Lorensa, Sintya; Damayanti, Farah A. A.; Barika, Fithri; Orlandoni, Muhammad R.; Mujiyana, Mujiyana (Prosiding Seminar Nasional Program Pengabdian Masyarakat, 2025)
Sukosreno Hamlet, located in Karangsari Village, Wonosobo, Central Java, has great potential in mushroom cultivation as an economic source for the community. However, mushroom cultivation in this area still faces several obstacles, such as suboptimal production quality, inadequate cultivation facilities, and limited marketing of the harvest. Therefore, the Regular Community Service Program (KKN) 131 in the odd semester of 2025 focuses on optimizing mushroom cultivation in Sukosreno Hamlet to increase community income and strengthen the role of Village-Owned Enterprises (BUMDes). The main objective of this activity is to improve the quality and quantity of mushroom production and assist the community in marketing strategies so that mushroom products are more competitive in the market. The targets of the activity include mushroom farmers and the local community. The methods used in this activity include several stages, namely (1) identifying problems through observation and discussion with the community, (2) renovating mushroom houses to create a more optimal cultivation environment, (3) handling caterpillar pests on mushrooms, and (4) counseling on marketing strategies, both conventionally through collaboration with markets and restaurants, and digitally through social media and marketplaces. The results of this activity show an increase in the quality of the mushroom house after renovation, which has an impact on the cultivation environment conditions that are more stable and conducive to mushroom growth. In addition, marketing counseling provides new understanding to farmers regarding more effective distribution strategies, which are expected to increase their sales and income. The success of this program is measured by the increase in mushroom production, active community participation in training, and the implementation of marketing strategies by farmers. The benefits of this activity are not only felt in the short term in the form of increased harvests and wider marketing, but also in the long term through increased economic independence of the community and the formation of a stronger marketing network. Thus, this program is expected to be the first step in developing the mushroom cultivation sector as one of the pillars of a sustainable village economy